NaCl: for the safer in vivo use of antibacterial silver based nanoparticles - Liu MZ; Zhang HQ; Song XW; Wei CC; Xiong ZF; Yu F; Li C; Ai FR; Guo GH; Wang XL (International Journal of Nanomedicine, 2018)
Mingzhuo Liu,1 Huiqing Zhang,1 Xiangwei Song,2 Chaochao Wei,2 Zhenfang Xiong,3 Fen Yu,2 Chen Li,4 Fanrong Ai,5 Guanghua Guo,1,* Xiaolei Wang2,* 1Department of Burns, The First Affiliated Hospital, Nanchang University, Nanchang, Jiangxi, China; 2Department of Translational Medicine, Nanchang University, Nanchang, Jiangxi, China; 3Department of Pathology, The First Affiliated Hospital, Nanchang University, Nanchang, Jiangxi, China; 4Department of Orthopedic Surgery, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, China; 5School of Mechanical & Electronic Engineering, Nanchang University, Nanchang, Jiangxi, China *These authors contributed equally to this work Background: As antibiotics progressively cease to be effective, silver based nanoparticles (SBNs), with broad antibacterial spectrum, might be the last line of defense against malicious bacteria. Unfortunately, there are still no proper SBNs-based strategies for in vivo antibacterial therapies. In this article, new carbon membrane packaged Ag nanoparticles (Ag-C) were synthesized. We assessed the effect of Ag-C with NaCl on size, cytotoxicity, antibacterial properties, metabolism and sepsis models.Methods: The size of Ag-C with NaCl was accessed with UV-vis, TEM and SEM. Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were used to illustrate the antibacterial properties of SBNs affected by NaCl. L929 and 3T3 cell lines were cultured in vitro; CCK-8 assay was used to test cytotoxicity. Then, we explored the metabolism of Ag-C with NaCl in vivo. Finally, the effect of Ag-C with 4× NaCl on sepsis was observed.Results: NaCl could regulate the size of Ag-C. Ag-C exhibited superior antibacterial properties compared to similar sized pure Ag nanoparticles. Furthermore, the addition of NaCl could not only reduce the cytotoxicity of Ag-C, but could also continue to discharge Ag-C from major organs. Based on these factors, this method was used to treat a sepsis model (induced via cecal ligation and puncture), and it achieved satisfactory survival results.Conclusion: This discovery, though still in its infancy, could significantly improve the safety and feasibility of SBNs and could potentially play an important role in modern in vivo antibacterial applications. Thus, a new method to combating the growing threat from drug-resistant bacteria could be possible. NaCl is the key to excretion of SBNs after in vivo antibacterial use. Keywords: Ag nanoparticles, NaCl, cytotoxicity, antibacterial, metabolism